FOREIGNIZATION AND DOMESTICATION AS TRANSLATION STRATEGIES: A COMPARATIVE ANALYSIS - Xolmurzayev , Oybek (Zamonaviy ta’lim va tilshunoslik rivoji, 2026)
This thesis analyses foreignization and domestication strategies in translation based on the theories of Friedrich Schleiermacher and Lawrence Venuti. The linguistic, cultural, and socio-political aspects of both approaches are examined, and their practical application is demonstrated through English-Uzbek literary translation examples. The findings justify the necessity of a balanced strategy selection depending on text type.